Profitability of Fertilizer: Experimental Evidence from Female Rice Farmers in Mali - Beaman, Lori; Karlan, Dean; Thuysbaert, Bram; Udry, Christopher (American Economic Review, 2013)
We conducted an experiment providing fertilizer grants to female rice farmers in Mali. We found that women who received fertilizer used both more fertilizer and more complementary inputs such as herbicides and hired labor. This shows that farmers respond to an increase in one input by re-optimizing other inputs. Second, while the increase in inputs led to a considerable increase in output, we found no evidence that profits increased. Our results suggest that fertilizer's impact on profits is small compared to other sources of variation. This may make it difficult for farmers to learn about the returns to fertilizer.